2012
DOI: 10.4236/ampc.2012.22013
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Electrical Properties of Polyaniline Composite with Silver Nanoparticles

Abstract: Polyaniline/silver (PANI/Ag) nanocomposite was prepared by chemical oxidative polymerization of aniline monomer in the presence of nitric acid. The formation of PANI/Ag nanocomposite was characterized by XRD, FTIR, TEM, UV-vis spectroscopy. The XRD patterns indicated that the crystalline phase of Ag is cubic with crystallite size of 93 nm. The TEM image shows that the Ag nanoparticles are well dispersed in the polyaniline matrix. Optical measurements show that the value of optical band gap of nanocomposite is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(79 citation statements)
references
References 11 publications
3
75
0
1
Order By: Relevance
“…As observed, for all the coatings, the ICR values were significantly affected by the number of coating cycles and especially for PANI coatings wherein the ICR seemed to be almost linearly dependant on the number of CV cycles for up to 20 coating cycles. As mentioned earlier, the expected increase in the ICR for PANI coated samples was due to the relatively low electrical conductivity of thicker PANI films as opposed to metals [36]. …”
Section: Effect Of Tin Np Loading and Coating Thicknessmentioning
confidence: 56%
“…As observed, for all the coatings, the ICR values were significantly affected by the number of coating cycles and especially for PANI coatings wherein the ICR seemed to be almost linearly dependant on the number of CV cycles for up to 20 coating cycles. As mentioned earlier, the expected increase in the ICR for PANI coated samples was due to the relatively low electrical conductivity of thicker PANI films as opposed to metals [36]. …”
Section: Effect Of Tin Np Loading and Coating Thicknessmentioning
confidence: 56%
“…They combine the electrical properties of metals with the advantage of polymers such as smaller weight, greater workability, resistance to corrosion and lower cost [1] hence can be regarded as suitable candidates for the replacement of metals [2]. Polyaniline PANI is one of the most useful of these polymers due to its easy synthesis, good environmental stability, reversible electrical properties and low cost of monomer [3,4]. Its high absorption coefficient in the visible part of the electromagnetic spectrum, high mobility of charge carriers and great stability has made it very attractive to scientific researchers [1].…”
Section: Introductionmentioning
confidence: 99%
“…This result indicated that the modification of carbon paste with nanofiber-polyaniline (110-120 nm) was effective in increasing the electroconductivity of the electrodes. The electroconductive property of polyaniline is caused by protonation in strong acid media when oxidative polymerization occurs [13]. The nano-size and fiber form of the polyaniline particle also influence its electroconductiveness because they contributed to a larger surface area of the electrodes [14].…”
Section: Cyclic Voltammetry Of Cpes and Mcpesmentioning
confidence: 99%